2020
DOI: 10.1016/j.jinf.2019.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Prioritising Hepatitis C treatment in people with multiple injecting partners maximises prevention: A real-world network study

Abstract: Objective: To describe an injecting network of PWID living in an isolated community on the Isle of Wight (UK) and the results of a agent-based simulation, testing the effect of Hepatitis C (HCV) treatment on transmission. Method: People who inject drugs (PWID) were identified via respondent driven sampling and recruited to a network and bio-behavioural survey. The injecting network they described formed the baseline population and potential transmission pathways in an agent-based simulation of HCV transmission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…However, a third modelling study from the United Kingdom (UK) has shown the opposite 7 . In this study degree‐based treatment partners reduced transmission and the overall prevalence of HCV at one year.…”
Section: Introductionmentioning
confidence: 70%
See 4 more Smart Citations
“…However, a third modelling study from the United Kingdom (UK) has shown the opposite 7 . In this study degree‐based treatment partners reduced transmission and the overall prevalence of HCV at one year.…”
Section: Introductionmentioning
confidence: 70%
“…We independently altered baseline prevalence, treatment coverage rate and the prevalence of receptive needle sharing (RNS) to test the effect on the primary outcome. Treatment coverage and baseline prevalence are known to have an important impact on TasP effects, 9 and change in RNS rate was found to be the greatest determinant of the relative effectiveness of different treatment strategies in a prior study 7 …”
Section: Methodsmentioning
confidence: 89%
See 3 more Smart Citations